Optimization of bioethanol production from sugarcane molasses by the response surface methodology using Meyerozyma caribbica isolate MJTm3 - Estifanos Hawaz; Mesfin Tafesse; Anteneh Tesfaye; Solomon Kiros; Dereje Beyene; Gessesse Kebede; Teun Boekhout; Marizeth Groenwald; Bart Theelen; Ayantu Degefe; Sisay Degu; Alene Admasu; et al. (Annals of Microbiology, 2023)
Abstract Purpose Yeast strains tolerant to a wide range of stress conditions are needed for the production of bioethanol from substrates rich in sugar. In our earlier research findings, Meyerozyma caribbica isolate MJTm3 (OM329077) demonstrated remarkable stress tolerance and fermentative activity. The present study aimed to optimize six fermentation parameters to generate conducive fermentation conditions for ethanol production by M. caribbica isolate MJTm3. Method The response surface method (RSM) based on central composite design (CCD) was employed to optimize process conditions for higher bioethanol yield. The optimization process was carried out based on six independent parameters, namely temperature (25–35 °C), pH (5.5–6.5), inoculum size (10–20% (v/v)), molasses concentration (25–35 (w/v)), mixing rate (110–150 rpm), and incubation period (48–72-h). Analysis of ethanol concentration was done by HPLC equipped with a UV detector. Result The optimal conditions of the parameters resulting in a maximum predicted ethanol yield were as follows: pH 5.5, an inoculum size of 20%, a molasses concentration of 25 °Bx, a temperature of 30 °C, an incubation period of 72-h, and a mixing rate of 160 revolutions per minute (rpm). Using the above optimum conditions, the model predicted a bioethanol yield of 79%, 92% of the theoretical yield, a bioethanol concentration of 49 g L−1, and a productivity of 0.68 g L−1 h−1. A batch fermentation experiment was carried out to validate the predicted values and resulted in a bioethanol yield of 86%, 95% of theoretical yield, a bioethanol concentration of 56 g L−1, and productivity of 0.78 g L−1 h−1. On the other hand, the surface plot analysis revealed that the synergistic effect of the molasses concentration and the mixing rate were vital to achieving the highest bioethanol yield. These values suggested that the RSM with CCD was an effective method in producing the highest possible output of bioethanol from molasses in actual operation. Conclusion The study confirmed the potential of using M. caribbica isolate MJTm3 for bioethanol production from sugarcane molasses under the abovementioned optimal fermentation conditions.